The Influence Of Good Corporate Governance And Company Size On The Financial Performance Of Banking Companies Listed On The IDX - Maria Rineldis Maru; Diana Airawaty (SEAN Institute, 2024)
This study aims to examine the effect of Good Corporate Governance (GCG) and firm size on the financial performance of companies. Financial performance is one of the main indicators of a company's success in maintaining competitiveness and attracting investors, especially in the banking sector. Good Corporate Governance is believed to be one of the important mechanisms that can influence the effective management of company resources, while firm size is often associated with the company's ability to manage assets and capital. The data in this study were obtained using the documentation method, which involves the collection and analysis of secondary data. This study uses financial report data from banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sampling method used in the data collection was purposive sampling, with a total sample of 99 banking sector companies. The results of the study show that the board of commissioners, board of directors, and audit committee have no effect on the company's financial performance, while firm size has a significant effect on the company's financial performance.